Análise de ambientes computacionais para realização de educação a distância - Falsarella, Sueli Aparecida (2010)
In recent decades, crescent development of technology has caused an imbalance between the teaching-learning methodology and access to these new resources. As a growing number of users who use the Internet via computer or mobile phone, there is a growing demand for new knowledge through virtual learning environments (VLE). This software can collaborate in the teaching-learning process, but barriers still exist for those who want to study or teach through technology. This research makes a study on the use of virtual learning environment Moodle, which offered advantages and disadvantages. According to research data, the results obtained with the use of the environment revealed the lack of trained teachers, and hence no interaction of these with their students. This delay hinders the optimal use of the environment which could contribute greatly to the construction of knowledge. This difficulty occurred since the early deployment of the environment in PUC / SP, Campus Sorocaba. Research shows, however, its implementation can be further adjusted and improved if there are incentives for those who deposited the environment and specific training for teachers that will encourage students to use it. Certification of use of the environment for curriculum, reading and questionnaire prior to classes to make better use of questioning and learning processes encourage students to make use of this new virtual learning environment